Using Expert Judgment to Assess Adaptive Capacity to Climate Change: Evidence From a Conjoint Choice Survey - Anna Alberini; Aline Chiabai; Lucija Muehlenbachs (Fondazione Eni Enrico Mattei (FEEM), 2005)
We use conjoint choice questions to ask public health and climate change experts, contacted at professional meetings in 2003 and 2004, which of two hypothetical countries, A or B, they deem to have the higher adaptive capacity to certain effects of climate change on human health. These hypothetical countries are described by a vector of seven attributes, including per capita income, inequality in the distribution of income, measures of the health status of the population, the health care system, and access to information. Probit models indicate that our respondents regard per capita income, inequality in the distribution of income, universal health care coverage, and high access to information as important determinants of adaptive capacity. A universal-coverage health care system and a high level of access to information are judged to be equivalent to 12,000-14,000 in per capita income. We use the estimated coefficients and country sociodemographics to construct an index of adaptive capacity for several countries. In panel-data regressions, this index is a good predictor of mortality in climatic disasters, even after controlling for other determinants of sensitivity and exposure, and for per capita income. We conclude that our conjoint choice questions provide a novel and promising approach to eliciting expert judgments in the climate change arena.
Keywords: Q54; I18; 330; Adaptive capacity; Climate change; Human health effects; Extreme events; Heat waves; Vector-borne illnesses; Conjoint choice; Vulnerability; Sensitivity; Klimaveränderung; Gesundheitsrisiko; Sachverständige; Conjoint-Analyse